Comprehensive analysis of non-motor symptoms and their association with quality of life in Writer's cramp. (July 2022) - Zhang, Lingyu; Hou, Yanbing; Lin, Junyu; Yang, Jing; Cao, Bei; Wei, Qianqian; Ou, Ruwei; Shang, Huifang
Abstract: Objective: Limited studies have focused on non-motor symptoms (NMS) in patients with Writer's cramp (WC). The current study aimed to examine the frequency of NMS and their association with health-related quality of life (HR-QoL) in patients with WC. Methods: A total of 80 patients with WC and 69 healthy controls (HCs) were enrolled. Motor symptoms was assessed by Burke-Fahn-Marsden dystonia rating scale and NMS was evaluated through several specific scales, including Hamilton depression rating scale-24 items (HDRS-24), Hamilton anxiety rating scale, Epworth sleepiness scale, Pittsburgh sleep quality index, fatigue severity scale (FSS), numerical rating scale for pain, and Montreal cognitive assessment. The HR-QoL was assessed using 36-item short form health survey (SF-36), which can be divided into physical component summary (PCS) and mental component summary (MCS). Multiple linear regression was used to analysis the association between each NMS and HR-QoL. Results: The patients presented more symptoms of depression, anxiety, poor quality of sleep, excessive daytime sleepiness, and fatigue than the HCs. The most frequent NMS in patients with WC was anxiety (51.25%) and depression (46.25%) symptoms. We found that motor symptoms had no association with HR-QoL. Higher scores of HDRS-24 were associated with lower scores of SF-36 in PCS and MCS. Meantime, higher scores of FSS were significantly associated with lower scores of SF-36 in MCS. Conclusion: The NMS was prevalent in patients with WC, with frequent anxiety and depression symptoms. Depression symptoms and fatigue had a strongly negative impact on HR-QoL and deserve attention in clinic practice. Highlights: The most frequent NMS in patients with WC was anxiety and depression symptoms. Motor symptoms had no association with HR-QoL. Depression symptoms and fatigue were major determinants of HR-QoL in WC patients.